Maxillary sinus augmentation: collagen membrane over the osteotomy window. A pilot study - F.S. Marchionni; F. Alfonsi; S. Santini; S. Marconcini; U. Covani; A. Barone (Ariesdue, 2015)
Aim Implant rehabilitation has become a very reliable and safe procedure. However, in some cases, a small amount of bone could make implant surgery extremely difficult or even impossible. Hence, a surgical technique to augment sinus floor has been developed and improved. Nevertheless, there is still controversy over the use of a membrane over the osteotomy window. Therefore, the aim of this study was to investigate whether the use of a membrane could be beneficial in sinus floor augmentation. Materials and methods A group of 12 patients requiring sinus floor lift were recruited. The patients were randomly allocated to either control group (membrane) or test group (no membrane) and only one sinus for patient was augmented. After 6 months, a bone biopsy was harvested from the lateral window to be processed for histological analysis. Results The mean amount of newly formed bone in test group was 28.0±19.5%, the connective tissue accounted for a mean value of 59.2±15.6%, while 12.8±12.6% was the amount of residual graft particles. In the membrane group the newly formed bone counted for a mean value of 30.4±15.8%, the mean quantity of connective tissue was 50.3±18.9% and about residual graft particles a mean value of 18.2±20.4% was registered. Conclusion According to our data, the use of a membrane over the lateral bone wall in sinus lift surgery does not significantly influence healing. However, the membrane could influence the residual particles resorption rate as well as soft tissue ingrowth.